Sor Juana and the Countess of Villaumbrosa - Finley, Sarah (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
Along with Christina of Sweden and the Duchess of Aveiro, the Countess of Villaumbrosa María Petronila Niño de Porres Enríquez de Guzmán is one of three contemporary thinkers from Sor Juana Inés de la Cruz’s catalogue of learned women in the Respuesta a Sor Filotea. Despite the other two’s political and intellectual prominence, prior research overlooks the Countess. In response, my study presents the first intellectual biography of María Petronila. It deepens understanding of Sor Juana’s transatlantic networks and also draws attention to a scholar that lends insight into women’s participation in lettered circles throughout the early modern world.